Associations between major depressive disorder and performance-based and self-reported music cognition - Treviño-Soto, Mariana; Gorozpe-Camargo, Santiago; Cejudo-Camarena, Álvaro; Fernández-Palacios, María Elena; Uzárraga-Andrade, Ana Claudia; Alamillo-Cuéllar, Ana Isabel; Toledo-Fernández, Aldebarán (Frontiers in Psychology, 2024)
Background There is evidence that major depressive disorder (MDD) comes with multiple cognitive impairments including deficits in perception and memory. Music cognition is one of the least explored cognitive functions in relation to MDD, with some studies pointing to mild amusic deficits. These findings, however, are derived only from performance-based tests. Our objectives were to explore differences in music perception and memory between individuals with MDD and a control group, in both performance test and self-report of amusic dysfunction, and to assess the correlation between these measures. Method We recruited 62 participants, including MDD individuals (n = 34) diagnosed with the Mini International Neuropsychiatric Interview and controls (n = 18). All the participants were evaluated with the Montreal Battery for Evaluation of Amusia (MBEA) and the Amusic Dysfunction Inventory (ADI). Results None of the assessed dimensions from the MBEA or the ADI showed statistical differences between groups. Some significant associations were found between ADI's Vocal Production and the MBEA's three tests of the melodic dimension (Scale, Contour and Interval) and between MBEA's Scale and Memory, Meter and ADI's Melodic Perception, and tests of Memory from each respective instrument. Conclusion Results suggest that perception and memory of basic music stimuli are not among the cognitive deficits within MDD, however, they may be indirectly affected by other cognitive phenomena common to this psychopathology, such as poor sustained concentration due to mental fatigue.